Phenotypic Detection of Carbapenemase Production in Carbapenem-Resistant Enterobacteriaceae by Modified Hodge Test and Modified Strip Carba NP Test - Patidar, Nisha; Vyas, Nitya; Sharma, Shanoo; Sharma, Babita (Journal of Laboratory Physicians, 2021)
Objective Carbapenems are last resort antibiotics for multidrug-resistant Enterobacteriaceae. However, resistance to carbapenem is increasing at an alarming rate worldwide leading to major therapeutic failures and increased mortality rate. Early and effective detection of carbapenemase producing carbapenem-resistant Enterobacteriaceae (CRE) is therefore key to control dissemination of carbapenem resistance in nosocomial as well as community-acquired infection. The aim of present study was to evaluate efficacy of Modified strip Carba NP (CNP) test against Modified Hodge test (MHT) for early detection of carbapenemase producing Enterobacteriaceae (CPE).Material and MethodsEnterobacteriaceae isolated from various clinical samples were screened for carbapenem resistance. A total of 107 CRE were subjected to MHT and Modified strip CNP test for the detection of CPE.Statistical Analysis It was done on Statistical Package for the Social Sciences (SPSS) software, IBM India; version V26. Nonparametric test chi-square and Z-test were used to analyze the results within a 95% level of confidence.Results Out of 107 CRE, 94 (88%) were phenotypically confirmed as carbapenemase producer by Modified strip CNP test and 46 (43%) were confirmed by Modified Hodge Test (MHT). Thirty-eight (36%) isolates showed carbapenemase production by both MHT and CNP test, 56 isolates (52%) were CNP test positive but MHT negative, eight (7%) isolates were MHT positive but CNP test negative and five (5%) isolates were both MHT and CNP test negative. There is statistically significant difference in efficiency of Modified CNP test and MHT (p < 0.05).Conclusion Modified strip CNP test is simple and inexpensive test which is easy to perform and interpret and gives rapid results in less than 5 minutes. It has high degree of sensitivity and specificity. Modified strip CNP test shows significantly higher detection capacity for carbapenemase producers as compared with MHT.
Keywords: carbapenem-resistant Enterobacteriaceae; carbapenemase producing Enterobacteriaceae; modified Hodge test; modified strip Carba NP test